Media and violence - Simon Burton (Communicare)
Based on extensive survey research work, this paper sets out to explore some comparative issues on the Impact of the media on attitudes to wards political violence in the Natal Midlands. Central to the discussion Is an attempt to apply and develop contemporary theories of the role of space, community and domestic ar rangements as a basis for exploring the differential Influence/impact of media representations of political violence. While an empirical approach, on its own, has many limitations in ex plaining how media representations shape attitudes, this paper sets out to show that the media "consump tlon" of Whites and Indians' poses a number of important questions for researchers of medla effects